Ultrathin epitaxial NbN superconducting films with high upper critical field grown at low temperature. Issue 8 (3rd August 2021) - Wei, Xiucheng; Roy, Pinku; Yang, Zihao; Zhang, Di; He, Zihao; Lu, Ping; Licata, Olivia; Wang, Haiyan; Mazumder, Baishakhi; Patibandla, Nag; Cao, Yong; Zeng, Hao; et al.
Abstract : Ultrathin (5–50 nm) epitaxial superconducting niobium nitride (NbN) films were grown on AlN-buffered c -plane Al2 O3 by an industrial scale physical vapor deposition technique at 400°C. Both X-ray diffraction and scanning electron microscopy analysis show high crystallinity of the (111)-oriented NbN films, with a narrow full-width-at-half-maximum of the rocking curve down to 0.030°. The lattice constant decreases with decreasing NbN layer thickness, suggesting lattice strain for films with thicknesses below 20 nm. The superconducting transition temperature, the transition width, the upper critical field, the irreversibility line, and the coherence length are closely correlated to the film thickness. GRAPHICAL ABSTRACT: IMPACT STATEMENT: This work realized high quality ultrathin epitaxial NbN films by an industry-scale PVD technology at low substrate temperature, which opens up new opportunities for quantum devices.